2016
DOI: 10.1007/s00425-016-2517-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of a new wheat-rye 1BL•1RS translocation line expressing superior stripe rust resistance and enhanced grain yield

Abstract: A new wheat-rye 1BL•1RS translocation line, with the characteristics of superior stripe rust resistance and high thousand-kernel weight and grain number per spike, was developed and identified from progenies of wheat-rye- Psathyrostachys huashanica trigeneric hybrids. The wheat-rye 1BL•1RS translocation line from Petkus rye has contributed substantially to the world wheat production. However, due to extensive growing of cultivars with disease resistance genes from short arm of rye chromosome 1R and coevolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…These new T1RS.1BL translocation lines showed diversity-resistant patterns to rust stripe and powdery mildew. However, few new translocation lines showed both high resistance to these two diseases and could be used in the wheat breeding program (Ko et al, 2002; Yang et al, 2014; Li et al, 2016b; Qi et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new T1RS.1BL translocation lines showed diversity-resistant patterns to rust stripe and powdery mildew. However, few new translocation lines showed both high resistance to these two diseases and could be used in the wheat breeding program (Ko et al, 2002; Yang et al, 2014; Li et al, 2016b; Qi et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, due to its single origin, the 1RS chromosome arm derived from Petkus rye has not provided protection against the prevalence of virulent pathogens (Shi et al, 2001; Ren et al, 2009). So far, only a few other sources of 1RS were transferred into wheat (Ko et al, 2002; Mater et al, 2004; Ren et al, 2009, 2012; Molnár-Láng et al, 2010; Yang et al, 2014; Li et al, 2016a,b; Qi et al, 2016), and not every new translocation line could be used in wheat breeding programs (Ren et al, 2012). For more efficient use of the T1RS.1BL translocation in wheat breeding, Ren et al (2012) suggested introduce a large amount of new genetic variation from many different rye sources into wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Trigeneric hybrids seem to be less promising as potential crop, but they could be a useful bridge for the transference of chromatin into cultivated wheat. For example, Qi et al (2016) produced a new wheat-rye- Psathyrostachys trigeneric hybrid carrying the wheat-rye 1BL•1RS translocation and a cryptic translocation involving a small chromosome segment with the stripe rust resistance gene from P. huashanica . In this study, we developed two Triticum–Secale–Thinopyrum hexaploid lines that carried resistance genes against FHB, leaf rust, and stem rust race Ug99.…”
Section: Discussionmentioning
confidence: 99%
“…Wild relatives of common wheat, which have superior agronomic traits and resistance to biotic and abiotic stresses, are often used as desirable gene donors in wheat breeding programs (Dong et al, 1992; Mujeeb-Kazi et al, 2013). To date, many genes from wild species conferring superior traits have been transferred into cultivated wheat by developing newly synthesized allopolyploids (Qi et al, 2016). For example, breeders developed a man-made crop, triticale (X Triticosecale Wittmack), by crossing wheat ( T. turgidum or T. aestivum ) and rye.…”
Section: Introductionmentioning
confidence: 99%
“…Wild relatives of common wheat display numerous desirable agronomic traits, including strong adaptability, resistance to biotic and abiotic stress, and high-quality of wheat, and might thus potentially enrich the genetic repertoire of domesticated wheat species [4, 5]. Distant hybridization is a commonly used approach to modify the genetic background of common wheat in order to introduce the beneficial traits of wild species into the genome of domestic wheat [6, 7]. To date, numerous related species from the tribe Triticeae , including those from genera Aegilops , Agropyron , Dasypyrum , Hordeum , Leymus , Lophopyrum , Psathyrostachys , Secale , and Thinopyrum , have been successfully crossed with wheat, and the resulting cultivars have contributed significantly to wheat production worldwide [813].…”
Section: Introductionmentioning
confidence: 99%